Achieving a 3D thermally conductive while electrically insulating network in polybenzoxazine with a novel hybrid filler composed of boron nitride and carbon nanotubes - Wang, Yi; Wu, Wei; Drummer, Dietmar; Liu, Chao; Tomiak, Florian; Schneider, Kevin; Huang, Zhengqiang (Polymers, 2020)
To solve the problem of excessive heat accumulation in the electronic packaging field, a novel series of hybrid filler (BN@CNT) with a hierarchical “line-plane” structure was assembled via a condensation reaction between functional boron nitride(f-BN) and acid treated carbon nanotubes (a-CNTs). The reactions with different mass ratios of BN and CNTs and the effect of the obtained hybrid filler on the composites’ thermal conductivity were studied. According to the results, BN@15CNT exhibited better effects on promoting thermal conductivity of polybenzoxazine(PBz) composites which were prepared via ball milling and hot compression. The thermally conductive coefficient value of PBz composites, which were loaded with 25 wt% of BN@15CNT hybrid fillers, reached 0.794 W·m−1·K−1. The coefficient value was improved to 0.865 W·m−1·K−1 with 15 wt% of BN@15CNT and 10 wt% of BN. Although CNTs were adopted, the PBz composites maintained insulation. Dielectric properties and thermal stability of the composites were also studied. In addition, different thermal conduction models were used to manifest the mechanism of BN@CNT hybrid fillers in enhancing thermal conductivity of PBz composites.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Fillers; Functionalization of polymers; Nanocomposites; Networks

Expandable Graphite as a Multifunctional Flame-Retarding Additive for Highly Filled Thermal Conductive Polymer Formulations - Tomiak, Florian; Schneider, Kevin; Schoeffel, Angelina; Rathberger, Klaus; Drummer, Dietmar (Polymers, 2022)
Expandable graphite (EG) and graphite (G) were assessed as multifunctional additives improving both flame retardancy and thermal conductivity in highly filled, thermal conductive polymeric materials based on polyamide 6 (PA6). Fire testing was conducted using modern UL-94, LOI and cone calorimeter test setups. It is demonstrated that thermal conductivity can significantly influence the time to ignition, although offering little fire resistance once ignited even in highly filled systems. Thus, for PA6 formulations containing solely 70 wt.% G, the peak heat release rate (pHRR) measured in cone calorimeter tests was 193 kW/m(2), whereas PA6 formulations containing 20 wt.% EG/50 wt.% G did not exhibit a measurable heat development. Particular attention was paid to effect separation between thermal conductivity and residue formation. Good thermal conductivity properties are proven to be particularly effective in test scenarios where the heat impact is comparatively low and the testing environment provides good heat dissipation and convective cooling possibilities. For candle-like ignition scenarios (e.g., LOI), filling levels of >50 wt.% (G or EG/G) are shown to be sufficient to suppress ignition exclusively by thermal conductivity. V0 classifications in UL-94 vertical burning tests were achieved for PA6 formulations containing >= 70 wt.% G, >= 25 wt.% EG and >= 20 wt.% EG/25 wt.% G.
CRIS-Team WoS Importer:2022-05-06

Flame-retardant polyamide powder for laser sintering: Powder characterization, processing behavior and component properties - Schneider, Kevin; Wudy, Katrin; Drummer, Dietmar (Polymers, 2020)
Up to now, laser-sintered components have been barely used by industries such as aerospace and transport industry due to high flammability. By the use of flame retardants, the flammability of laser-sintered parts should be reduced to extend their range of possible applications. This paper aims to investigate the influence of halogen-free phosphinate-based flame retardants on process-relevant characteristics and process behavior, as well as mechanical and physical properties. Most importantly, the flammability of the material should be reduced. Two different types of phosphinate-based fillers were used in a concentration between 10 and 25 wt % in combination with the matrix material polyamide 12 (PA12). Thermal, optical, and powder properties of the mixtures were analytically investigated. Furthermore, the mechanical characterization of the sintered specimen was carried out. The addition of filler in laser sintering changes the process behavior and properties of the component. With this investigation, the correlation among flame retardants, process-relevant characteristics, process behavior, and resulting part properties was derived for the first time. Finally, a mixture of 15-20 wt % of flame retardant leads to the best trade-off between flame retardancy and mechanical properties.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Flame-retardant polymer; Flammability; Polyamide 12; Selective laser sintering

Highly thermally conductive polybenzoxazine composites based on boron nitride flakes deposited with copper particles - Wang, Yi; Wu, Wei; Drummer, Dietmar; Liu, Chao; Shen, Wanting; Tomiak, Florian; Schneider, Kevin; Liu, Xingrong; Chen, Qiming (Materials & Design, 2020)
To solve the heat diffusion problem in electronic packaging, a novel kind of irregularly shaped hybrid filler, boron nitride@copper (BN@Cu), was successfully assembled via reduction of Cu2+. BN@Cu hybrid fillers composed of different mass ratios between BN and Cu have been prepared and characterized. A specific BN@Cu hybrid filler (mBN:mCu = 100:2), labeled as BN@2Cu, exhibited remarkable ability in enhancing the thermal conductivity of polybenzoxazine (PBz) composites fabricated through ball milling followed by hot pressing. With 25 wt% of BN@2Cu hybrid fillers, the thermal conductivity of PBz composites reaches 1.049 W m−1 K−1. Dielectric properties, electrical conductivity, and curing behavior of the composites were also investigated. In addition, Foygel's thermal conduction model was employed to demonstrate the mechanism of BN@2Cu hybrid filler in improving thermal conductivity.
CRIS-Team Scopus Importer:2020-04-17
Keywords: Boron nitride; Contact resistance; Hybrid filler; Polybenzoxazine; Thermal conductivity

High-Precision Thin Wall Bipolar Plates for Fuel Cell Applications via Injection Compression Molding with Dynamic Mold Temperature Control - Roth, Benedikt; Frank, Rainer; Kleffel, Tobias; Schneider, Kevin; Drummer, Dietmar (Polymers, 2022)
In recent years, the demand for polymer compound solutions for the application of bipolar plates in polymer electrolyte membrane fuel cells (PEMFC) has increased continuously due to significant cost and lifetime advantages compared to metallic solutions. The main challenge of the compounds is the high filler content required to ensure sufficient electrical conductivity of the bipolar plates. The associated increase in viscosity and simultaneously increased thermal conductivity limit the conventional injection molding process in terms of achievable flow path length to wall thickness ratios (plate aspect ratio). In order to evaluate the extent to which highly modified electrically conductive polymer material systems can be processed into thin-walled and highly dimensionally stable bipolar plates, an injection compression molding process with dynamic mold temperature control (ICM-DT) has been developed. For this purpose, a compound was prepared from polypropylene (PP) and graphite-flakes. The compound was characterized with respect to the achieved filler content, the electrical conductivity, as well as the pressure-and temperature-dependent solidification range. The ICM-DT experiments were carried out by varying the maximum mold temperature and the compression force. In addition, the process was designed with multiple compression and decompression steps to account for a possible pressure-dependent solidification of the compound. The plates were characterized with respect to the achieved plate aspect ratio and the flow-path-dependent dimensional thickness stability. It was shown that the plate aspect ratio could be increased by up to 125% with the maximum filler content compared to conventional injection molding processes provided in the literature. With the multi-stage ICM-DT process, it was also possible to optimize the thickness dimensional stability with a maximum deviation of 3% over the flow path.
CRIS-Team Scopus Importer:2022-08-05
Keywords: bipolar plate; dynamic mold temperature control; fuel cell; injection compression molding; thin-wall injection molding

Hochgefüllte Kunststoffe: Neue Potenziale durch den Einsatz von Füllstoffen zur gezielten Eigenschaftsmodifikation - Drummer, Dietmar; Grützmacher, Constanze; Kleffel, Tobias; Lanzl, Lydia; Rösel, Uta; Roth, Benedikt; Schneider, Kevin; Tomiak, Florian; Wittmann, Lisa-Maria (Jahresmagazin Ingenieurwissenschaften, 2021)
Die Anforderungen an Kunststoffbauteile erfordern meist den Einsatz von Füll- und Verstärkungsstoffen sowie Additiven zur gezielten Modifikation des Eigenschaftsprofils. In diesem Beitrag werden aktuelle Forschungsschwerpunkte des Lehrstuhls für Kunststofftechnik (LKT) in der Verbesserung von mechanischen Eigenschaften und dem gezielten Einstellen von flammschützenden, elektrischen, dielektrischen und magnetischen Eigenschaften zur Bauteilfunktionalisierung vorgestell
Keywords: Gefüllte Systeme in der AF; Flammschutz durch synergistische Wirkstoff-Kombinationen; Mehrschichtfolienextrusion; Thermoformen; Bipolarplatte; dreidimensionale Schaumstoffbauteile im Hochfrequenzschweißverfahren; Duroplastbasierte Kunststoffgebundene Dauermagnete

Improvement of thermal conductivity and mechanical properties for polybenzoxazine composites via incorporation of epoxy resin and segregated structure - Wang, Yi; Wu, Wei; Drummer, Dietmar; Liu, Chao; Tomiak, Florian; Schneider, Kevin (Materials Research Express, 2020)
Developing tendency of increasing integration in electronic components filed led to the demand for thermally conductive polymer materials. Forming a segregated structure with thermally conductive fillers in the matrix has been proven to be a promising technique. However, the mechanical properties of the material prepared via this technique are commonly sacrificed because the interaction between fillers and matrix are weak. We present a simple method to improve the mechanical properties while maintaining the segregated structure via the collaboration of epoxy and polybenzoxazine(PBz). The fillers, epoxy resin, and benzoxazine(BOZ) were mixed and then hot pressed under 12 MPa of pressure with a certain heating strategy. The thermal conductivity, density, mechanical properties, morphology, and thermal stability of the composites were investigated. With 25 wt% filler, the value of thermal conductivity coefficient of EP/PBz composites reached 0.811 W mK(-1), while that of PBz composites was 0.762 W mK(-1). The tensile strength of the matrix improved from 58.3 MPa to 99.7 MPa.
CRIS-Team WoS Importer:2020-10-02

RF Welding of Dielectric Lossless Foam Particles by the Application of a Dielectric Heatable Coating with High Recycling Potential - Schneider, Kevin; Kleffel, Tobias; Drummer, Dietmar (Polymers, 2023)
Due to its chemical structure and the resulting dielectric properties, the processing of the commonly used particle foam material, expanded polypropylene (ePP), is limited. Processing within the radio-frequency welding process is therefore only possible with the use of processing aids. In this paper, a new approach for the use of a solid and dielectric heatable coating for the production of three-dimensional welded components out of ePP is presented. For this purpose, three different types of water-soluble polymer polyvinyl alcohol (PVA) were analyzed as potential coating materials. The thermal and dielectric properties of the coating were further adjusted by a modification with glycerol. The maximum amount of glycerol tested was 25% by volume. It influences both the temperature development in the radio-frequency (RF) welding process as well as the adhesive bond between the ePP foam particles. It is shown that the 120 °C approach in the RF welding process resulted in a cohesive bond between the coating layers. In this way, bonded plates can be produced. In mechanical tests with compression of 20%, the manufactured plates show sufficient load capacity. Furthermore, it can be shown that a separation of PVA and ePP by type, and thereby a separation of the foam particles, is possible with the use of hot water. This might open a new way for recycling of particle foams.
CRIS-Team Scopus Importer:2023-10-20
Keywords: coating; dielectric loss; high-frequency welding; plastic foams; plasticizer; recyclability; water-soluble

Significantly enhanced thermal conductivity of polymer composites via establishing double-percolated expanded graphite/multi-layer graphene hybrid filler network - Liu, Chao; Wu, Wei; Drummer, Dietmar; Wang, Yi; Chen, Qiming; Liu, Xingrong; Schneider, Kevin (European Polymer Journal, 2021)
Utilization of hybrid fillers with high thermal conductivity enhancement (TCE) efficiency is an effective method for the large-scale fabrication of polymeric thermal interface materials (TIMs) with exceptional thermal conductivity. Herein, we report the thermally conductive properties of thermoplastic urethane (TPU) composites incorporated with expanded graphite (EG) and multi-layer graphene (MLG). The effect of percolation behavior of EG/MLG hybrid fillers on the thermal conductivity is systematically revealed. It is found that the high-loading TPU composite with 20 wt% EG and 10 wt% MLG reveals an exceptional thermal conductivity of 8.52 Wm(-1)K(-1), which corresponds to a TCE of 3450% compared to that (0.24 Wm(-1) K-1) of pure TPU matrix. Notably, the TCE per 1 wt% filler reaches a substantial value of 115%. The thermally conductive mechanism is proposed based on morphology and thermal contact resistance analyses. Moreover, the application of such TPU composites in thermal management of light-emitting diode lamps is exhibited, and the effectiveness is further verified through finite element simulation. Our results shed light on the significant thermal synergy between EG and MLG and demonstrate their application potential in high-performance TIMs.
CRIS-Team WoS Importer:2021-10-29

Simulative study of polymeric core-shell foam particles for the enlargement of the material portfolio in 3-D high-frequency welding - Schneider, Kevin; Ott, Constantin; Drummer, Dietmar (Polymer Engineering and Science, 2021)
The steam chest molding process is currently state of the art concerning the generation of three-dimensional polymeric foam components made from particle foams. An adaption of the high-frequency welding process shows advantages regarding the required energy and the used water. Due to the low dielectric loss factors of the most common foam materials (PE, PP, and PS), they cannot be heated sufficiently by an electric field. To enable heating of these foams, the particles may be coated with a second material that shows a high dielectric loss. The possible heat development of the modified particles was simulatively investigated. To ensure a realistic simulation, the properties of the used materials are analyzed beforehand. The heating simulation shows clear dependence regarding the particle size and the shell thickness. By a suitable combination, sufficient heating is achievable. For single particles, an irregular temperature distribution is calculated, mainly caused by the difference of permittivity resulting in a local variation of electrical flux density. Bigger particles and thicker shells will result in faster heating ramps and higher overall temperatures. The additional calculation regarding a particle-particle interaction shows a homogenization of the temperature distribution across the particle surface.
CRIS-Team WoS Importer:2021-12-17

The effect of dielectric and thermal properties of plastic mold materials on the high frequency welding of three-dimensional foam components - Schneider, Kevin; Gothe, Bastian; Drexler, Maximilian; Siltamaeki, Jarkko; Weiger, Helge; Seefried, Andreas; Drummer, Dietmar (Polymer Engineering and Science, 2022)
High-frequency heating processes are widely used in industry, for example, for food processing, wood drying, or plastic welding. A recent development in this field uses radio-frequency heating to fuse particle foam beads to complex components. The aim of using the modified process is to reduce the energy consumption of particle foam fusion. Within this process, the molds used must be electrically insulating to ensure the building of an electrical field. For this purpose, mold made of two different plastics were analyzed. Additional to the dielectric, mechanical, and thermal expansion, the thermal conductivity of the mold materials are of great interest. Although welding is finished quickly, cooling to the demolding temperature is comparably long. To achieve shorter cooling and therefore shorter process times, the mold materials were modified by two different thermal conductive but electrically insulating fillers. By the use of the thermally optimized mold materials, a reduction in cooling time of up to 40% was possible. At the same time, the heating step was hardly affected. Mechanical properties were enhanced while thermal expansion was reduced.
CRIS-Team Scopus Importer:2022-08-19
Keywords: dielectric properties; high-frequency welding; plastic foams; thermal conductivity

ZnO nanowire-decorated Al2O3hybrids for improving the thermal conductivity of polymer composites - Liu, Chao; Wu, Wei; Drummer, Dietmar; Shen, Wanting; Wang, Yi; Schneider, Kevin; Tomiak, Florian (Journal of Materials Chemistry C, 2020)
Thermal management is considered a crucial feature for the efficient integration of electronic devices; therefore, the requirement for polymer materials with excellent thermal conductivity is increasing. In this study, we designed and synthesized a novel hybrid filler composed of Al2O3spheres and needle-like zinc oxide nanowires, and then used it for the fabrication of thermally conductive polydimethylsiloxane (PDMS) composites. Furthermore, to sufficiently investigate the impact of the ZnO nanowire morphology on the thermal transfer ability of the composites, the aspect ratio of the nanowires was controlled by regulating the parameters of the hydrothermal reaction. The chemical structures and morphologies of the Al2O3-ZnO nanowire hybrids were confirmed by X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD) and scanning electron microscopy (SEM). The results indicated that the PDMS hybrid composites incorporated with 40 vol% hybrid filler decorated with high AR ZnO nanowires achieved the highest thermal conductivity of 1.185 W m-1K-1, which was about 6.77 times that of the pure PDMS matrix, and 46% higher than that of the Al2O3/PDMS composites. In addition, the hybrid filler also had positive influences on the mechanical property, thermal and dimensional stability of the PDMS composites due to its unique needle-like nanostructures. Our research demonstrated that the novel Al2O3-ZnO nanowire hybrid filler is an excellent candidate for the modification of thermal interface materials, which can be utilized in the thermal management of electronics.
CRIS-Team Scopus Importer:2020-05-15